2021
DOI: 10.3389/fimmu.2021.675186
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Need to Understand Very Early Onset Inflammatory Bowel Disease

Abstract: Very Early Onset Inflammatory Bowel Disease (VEO-IBD) represents a cohort of inflammatory bowel disease (IBD) patients diagnosed before 6 years of age. Unlike IBD diagnosed at older ages, VEO-IBD can be associated with underlying primary immunodeficiencies. VEO-IBD has been linked to monogenic variations in over 70 genes involved in multiple pathways of immunity. As sequencing technologies and platforms evolve and become readily available, an increasing number of genes linked to VEO-IBD have emerged. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…But the increased access to exome sequencing technology, which can effectively screen up to 200,000 exons, has rapidly expanded this list to 75 genes ( 10 , 11 ). All of these new genes play a role in immune dysregulation ( IL-10, Foxp3, STAT1, and TRIM22 ), T and B cell defects ( BTK, PIK3R1, ICOS, LRBA,IL21 , and DKC1 ), hyper and auto-inflammatory conditions ( CYBB,NCF,LACC1,SL37A4,ITGB2 ), and epithelial barrier dysfunction ( ADAM17, COL7A1,GUCY2C,IKBKG,TTC7A ) ( 6 , 10 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…But the increased access to exome sequencing technology, which can effectively screen up to 200,000 exons, has rapidly expanded this list to 75 genes ( 10 , 11 ). All of these new genes play a role in immune dysregulation ( IL-10, Foxp3, STAT1, and TRIM22 ), T and B cell defects ( BTK, PIK3R1, ICOS, LRBA,IL21 , and DKC1 ), hyper and auto-inflammatory conditions ( CYBB,NCF,LACC1,SL37A4,ITGB2 ), and epithelial barrier dysfunction ( ADAM17, COL7A1,GUCY2C,IKBKG,TTC7A ) ( 6 , 10 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric IBD makes up a quarter of all diagnosed IBD, and a subset of these cases occur in patients <6 years of age [ 26 ]. These are termed very early-onset IBD (VEOIBD) and are generally thought to have a simpler genetic basis [ 27 , 28 , 29 ]. VEOIBD has also been associated with PIDs, both through symptoms as well as gene involvement [ 23 , 28 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous exome studies of patients with VEOIBD have identified monogenic causes for a small percentage, but most cases remain without a genetic diagnosis. Monogenic cases of VEOIBD are more likely to have family history of IBD or immunodeficiencies and to be more severe and resistant to conventional treatment [ 27 , 28 ]. Research has also found patients with VEOIBD to have a higher rate of variants in genes associated with PIDs [ 31 ], suggesting that some cases for which a monogenic origin is not identified may have a multigenic etiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATG16L1 mutations results in dysfunctional autophagy, as evidenced by impaired ability of macrophages to clear intracellular bacteria and Paneth cells to secrete antimicrobial peptides ( 14 ). Furthermore, genetic variants in interleukin-10 (IL-10), IL-10 receptor(IL-10R), X-linked inhibitor of apoptosis protein (XIAP), and forkhead box P3 (FOXP3) have been linked to very early-onset inflammatory bowel disease (VEOIBD) ( 15 ). Deep sequencing studies and studies including large samples of patients with IBD are likely to generate additional knowledge on genetic variations in IBD, which will further highlight the complex genetic polymorphisms involved in this condition.…”
Section: Introductionmentioning
confidence: 99%